Thrombin induces morphological and inflammatory astrocytic responses via activation of PAR1 receptor - Xiaojun Chen; Han Zhang; Huifei Hao; Xingyuan Zhang; Honghua Song; Bingqiang He; Yingjie Wang; Yue Zhou; Zhenjie Zhu; Yuming Hu; Yongjun Wang (Cell Death Discovery, 2022)
Abstract Spinal cord injury (SCI) will result in the significant elevation of thrombin production at lesion site via either breakage of blood-spinal cord barrier or upregulated expression within nerve cells. Thrombin-induced activation of the protease activated receptors (PARs) evokes various pathological effects that deteriorate the functional outcomes of the injured cord. The cellular consequences of thrombin action on the astrocytes, as well as the underlying mechanism are not fully elucidated by far. In the present study, SCI model of rats was established by contusion, and primary astrocytes were isolated for culture from newborn rats. The expression levels of thrombin and PAR1 receptor at lesion sites of the spinal cord were determined. The primary astrocytes cultured in vitro were stimulated with different concentration of thrombin, and the resultant morphological changes, inflammatory astrocytic responses, as well as PAR1-activated signal pathway of astrocytes were accordingly examined using various agonists or antagonists of the receptor. Thrombin was found to reverse astrocytic stellation, promote proliferation but inhibit migration of astrocytes. Furthermore, the serine protease was shown to facilitate inflammatory response of astrocytes through regulation of MAPKs/NFκB pathway. Our results have provided the morphological evidence of astrocytic reactivity in response to thrombin stimulation and its neuroinflammatory effects following SCI, which will be indicative for the fundamental insights of thrombin-induced neuropathology.